Mulan’s (2020) Reflection: Evidences of Gender-Based Critical Thinking, A Path to Gender Equality - Dewi Puspitasari; Khusnul Alimah; Agnes Widyaningrum; Masrurotul; Zaimatus Sadiyah (MUWAZAH : jurnal kajian gender, 2022)
The purpose of this study was to examine how gender equality and inequality are represented in the film of Mulan (2020), a film which is based on the Chinese legend of Hua Mulan. The researchers aimed to explore the potential impact of the film's messages on viewers' cognitive and emotional levels, as it portrays the female protagonist as an active participant in the story and carries a strong feminist message. Unlike some other films, Mulan is not objectified or depicted as a source of eroticism, but rather as a proactive character fighting for fairness. To achieve the objective, the study employed a descriptive qualitative method and drew on Kate Millet's feminist theory. This theoretical framework was used to analyze and uncover the film's messages regarding gender equality. The researchers followed a four-step process involving data identification, classification, analysis, and drawing conclusions. Through their analysis, the study revealed a feminist movement that emerges from the main character and those around her, providing support for her pursuit of gender equality. The film also conveys valuable moral values related to gender equality and feminism, which can be applied in real-life contexts. The researchers anticipate that the findings of this study will contribute empirical evidence of gender equality and inequality practices depicted in the film.